Hernia inguinal en el niño. Revisión de 200 casos. - Celaya Venereo, Carlos; Morandeira Martín, Ángel; Morandeira Martín, Ángel; Martínez Canalejo, Arístides; Delgado Herrera, Carlos (Revista Cubana de Pediatría, 2023)
Trabajo preliminar basado en el estudio de 200 casos.